2014
DOI: 10.1002/ptr.5232
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Potential of L‐Sulforaphane in the Expression of Cytochrome P450 to Identify Potential Targets for Breast Cancer Chemoprevention and Therapy Using Breast Cell Lines

Abstract: The L-sulforaphane (SFN) component of broccoli sprout showed anticancer activity in several preclinical studies including breast cancer. Estrogens are considered major risk factors in breast carcinogenesis. The aim of this study was to evaluate the effect of SFN on the expression of cytochrome P450 involved in the estrogen metabolism in breast cancer cell lines MCF7 and MDA-MB-231 and in non-tumorigenic MCF10A cell line. The expression of CYP19, CYP1A1, 1A2, 1B1 was determined at the transcript and protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In addition to targeting Keap1, SFN can also enhance Nrf2 mRNA and protein expression by reducing methylation of the first 15 CpGs of Nrf2 promoters (82). Other targets of SFN, such as DNA methytransferases and histone deacetylase (83) are out of the scope of this review.…”
Section: Phytochemicals With Nrf2-are Activating Abilitymentioning
confidence: 99%
“…In addition to targeting Keap1, SFN can also enhance Nrf2 mRNA and protein expression by reducing methylation of the first 15 CpGs of Nrf2 promoters (82). Other targets of SFN, such as DNA methytransferases and histone deacetylase (83) are out of the scope of this review.…”
Section: Phytochemicals With Nrf2-are Activating Abilitymentioning
confidence: 99%
“…In addition to activating the Nrf2-Keap1 signaling pathway, sulforaphane exerts actions such as modulation of some major cytochrome P450 enzymes involved in xenobiotic metabolism. It has been reported that sulforaphane inhibited cytochrome P450 (CYP)1A1 and CYP1A2 enzymes induced by polycyclic aromatic hydrocarbons in HepG2 and MCF7 mammary cancer cells 23 ; inhibited CYP1B1 in MCF-10A cells 24 , inhibited CYP2B1/2 in rat hepatocytes 17 ; inhibited CYP3A4 in human hepatocytes 25 ; however, sulforaphane up-regulated CYP1A2 in MCF-10A cells 24 . The underlying mechanisms of the actions of sulforaphane on cytochrome P450 expression is unclear, but may relate in part to cross-talk between the Nrf2 and Aryl hydrocarbon receptor (Ahr) pathways 26 .…”
Section: Molecular Targets Of Sulforaphane: Not Just Nrf2mentioning
confidence: 99%
“…There was also no significant inhibitory effect of sulforaphane observed on CYP1A2 and on activities of other CYP enzymes in human liver microsomes (in concentrations up to 40 µM) (Langouet et al, 2000). On the other hand, an increased level of CYP1A2 mRNA and protein was observed in a study with human breast cell line MCF10, while an opposite effect was observed with CYP1A1 and CYP1B1 (Licznerska et al, 2015).…”
Section: Introductionmentioning
confidence: 59%